Bridging plate development for treatment of segmental bone defects of the canine mandible: Mechanical tests and finite element method - De Freitas, Elisângela Perez [UNESP]; Rahal, Sheila Canevese [UNESP]; Shimano, Antonio Carlos; Da Silva, Jorge Vicente Lopes; Noritomi, Pedro Yoshito; El-Warrak, Alexander Oliveira [UNESP]; Melchert, Alessandra [UNESP] (SAGE Publications, 2016)
With regard to the canine mandible, a mistaken concept of application is to assume that systemic plate-bone resistance is provided by the implant so that biomechanical position could be ignored. Because the alveolar border of the mandible is a tensile zone, the plate would ideally be positioned near this area while avoiding important structures. The aim of this study was to develop 2 bridging plates for the treatment of a segmental bone defect of the canine mandible using monocortical screws to avoid damage to the tooth roots and remaining neurovascular structures. Computed tomography images of the heads of 4 dogs (rottweiler, Doberman, boxer, and miniature poodle breeds) were used as models to develop the project. The images were reconstructed in 3-dimensional (3D) format. For each dog breed, 6 mandible prototypes were produced, each with a segmental bone defect in the right mandible. The mandibular reconstruction was performed with pure titanium bridging plate and locking screws. One plate model was developed for medium- and large-breed dogs and another for small-breed dogs. Mechanical testing showed the platemandible system resists the bite forces in all dog breeds. All safety factors were greater than 1 in the platemandible system for medium- and large-breed dogs and greater than 10 in the plate-mandible system for small-breed dogs. Thus, bridging plates designed with differentiated geometry and monocortical locking screws showed mechanical resistance to support simulated induced bone model defects and were able to support at least 5 times the value of bite force for each evaluated dog.
Keywords: Bridging plate; Canine orthopedics; Dog; Locking plate; Mandible; Mandibular bone defect